Generation of Fluorinated Amychelin Siderophores against Pseudomonas aeruginosa Infections by a Combination of Genome Mining and Mutasynthesis. Issue 12 (17th December 2020) - Xie, Feng; Dai, Shengwang; Zhao, Yu; Huang, Pei; Yu, Shen; Ren, Biao; Wang, Qiushui; Ji, Zengchun; Alterovitz, Gil; Zhang, Qi; Zhang, Jingyu; Chen, Xiangyin; et al.
Summary: Pioneering microbial genomic surveys have revealed numerous untapped biosynthetic gene clusters, unveiling the great potential of new natural products. Here, using a combination of genome mining, mutasynthesis, and activity screening in an infection model comprising Caenorhabditis elegans and Pseudomonas aeruginosa, we identified candidate virulence-blocking amychelin siderophore compounds from actinomycetes. Subsequently, we developed unreported analogs of these virulence-blocking siderophores with improved potency by exploiting an Amycolatopsis methanolica strain 239 T chorismate to salicylate a biosynthetic subpathway for mutasynthesis. This allowed us to generate the fluorinated amychelin, fluoroamychelin I, which rescued C . elegans from P . aeruginosa -mediated killing with an EC50 value of 1.4 μM, outperforming traditional antibiotics including ceftazidime and meropenem. In general, this paper describes an efficient platform for the identification and production of classes of anti-microbial compounds with potential unique modes of action. Graphical Abstract: Highlights: Actinobacteria is a fertile source of various types of siderophores The infection model can highlight the anti-infection but nonbactericidal siderophores The combinatory strategy is capable of identifying active siderophores The derivative fluoroamychelin I displays great anti- P . aeruginosa infection activity Abstract : Xie et al. have developed a combinatory strategy, including genome mining, mutasynthesis, and nematode high-throughput sequencing, and generated a new siderophore, fluoroamychelin I with potent activity of rescuing C . elegans from P . aeruginosa infection. This strategy provides an alternative approach to identify siderophores as useful therapeutic agents.